2022
DOI: 10.3389/fped.2022.828702
|View full text |Cite
|
Sign up to set email alerts
|

Thrombosis Complications in Pediatric Acute Lymphoblastic Leukemia: Risk Factors, Management, and Prevention: Is There Any Role for Pharmacologic Prophylaxis?

Abstract: Pediatric acute lymphoblastic leukemia (ALL) has achieved close to 90% cure rates through extensive collaborative and integrative molecular research, clinical studies, and advances in supportive care. Despite this high achievement, venous thromboembolic complications (VTE) remain one of the most common and potentially preventable therapy-associated adverse events in ALL. The majority of thromboses events involve the upper central venous system which is related to the use and location of central venous catheter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 107 publications
0
17
0
Order By: Relevance
“…CNS thrombosis has an important place in terms of symptomatic thromboembolic complications in patients with ALL 3,8 . Most studies investigating cases of thrombosis in patients with leukemia include data on cerebral sinus vein thrombosis (CSVT) because it is more common than arterial thrombosis 2,9 . Data on the frequency of arterial thrombosis are limited.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…CNS thrombosis has an important place in terms of symptomatic thromboembolic complications in patients with ALL 3,8 . Most studies investigating cases of thrombosis in patients with leukemia include data on cerebral sinus vein thrombosis (CSVT) because it is more common than arterial thrombosis 2,9 . Data on the frequency of arterial thrombosis are limited.…”
Section: Discussionmentioning
confidence: 99%
“…3,8 Most studies investigating cases of thrombosis in patients with leukemia include data on cerebral sinus vein thrombosis (CSVT) because it is more common than arterial thrombosis. 2,9 Data on the frequency of arterial thrombosis are limited. In a meta-analysis by Caruso et al, the incidence of CNS thrombosis was reported in 49 patients out of 1752 pediatric patients with leukemia (2.49%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations